Optimizing The Role of BUMDes Gemilang through Barista Training for Community Empowernment in Gagaksipat Village, Boyolali (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Gagaksipat Village, Ngemplak, Boyolali, has local economic potential through various micro-enterprises, particularly in the coffee business sector. However, limited skills and knowledge among the community have hindered the optimal utilization of this potential. To address this issue, a community service program conducted by the Faculty of Economics and Business implemented participatory-based barista training and coffee business mentoring. The program involved 35 local participants through interactive workshops, hands-on practice, and group discussions. As a result, participants demonstrated improved competencies in coffee brewing techniques, product innovation, and business management skills. Approximately 80% of participants (28 individuals) expressed motivation to explore coffee-related business opportunities. Furthermore, the program strengthened the institutional role of BUMDes Gemilang as a local economic driver by initiating collaborative marketing strategies. These findings indicate that participatory capacity-building activities not only enhance human resources but also contribute to sustainable local economic growth. This program may serve as a model for similar rural entrepreneurship development initiatives in other regions.